Caracterización de la comunidad de educación matemática de habla hispana: una aproximación desde su documentación de acceso abierto (2020)
The general objective of the research is to characterize the Spanish-speaking Mathematics Education community in terms of its thematic trends that are manifested in the open access documentation it produces. To achieve its development, a specific taxonomy was produced in Mathematics Education whose categories support the study variables. The thematic tendencies of the Spanish-speaking community were established in terms of the variables, and subcommunities of the Spanish-speaking Mathematics Education community were identified and compared according to the thematic focuses that characterize them. Eight sub-studies were carried out to fulfill the objectives of the research. These sub-studies are presented through a set of papers. One of the papers exposes the process of elaboration and validation of the new taxonomy of key terms of Mathematics Education. Two papers report on the development of the discipline in Spanish-speaking countries and on the thematic trends in its open-access documentation. Regarding the characterization of sub-communities, different approaches were made: from a specific educational level, from a country and the diversity of its documentation, from a mathematical content and from specific events. This last approach allowed the comparison of two sub-communities according to the thematic interest focuses that are evident in their reports.